Fatigue and failure mode analyses of glass infiltrated 5Y-PSZ bonded onto dentin analogues - Rodrigues, Jonas Vinicius Meireles [UNESP]; Demachkia, Amir Mohidin [UNESP]; da Silva de Assis, Rita Adriana Souza [UNESP]; Gomes, Mariana Marques [UNESP]; Campos, Tiago Moreira Bastos; Dapieve, Kiara Serafini; Valandro, Luiz Felipe; de Melo, Renata Marques [UNESP] (Springer Nature, 2024)
The purpose of this study was to evaluate the fatigue survival of 5Y-PSZ zirconia infiltrated with an experimental glass and bonded onto dentin analogues. Disc-shaped specimens of a 5Y-PSZ (Katana UTML Kuraray Noritake) were cemented onto dentin analogs (NEMA G10) and divided into four groups (n = 15): Zctrl Group (control, without infiltration); Zglz Group (Glaze, compression surface); Zinf-comp Group (Experimental Glass, compression surface); Zinf-tens Group (Experimental Glass, tension surface). Surface treatments were varied. Cyclic fatigue loading, oblique transillumination, stereomicroscope examination, and scanning electron microscopy were performed. Fatigue data were analyzed (failure load and number of cycles) using survival analysis (Kaplan–Meier and Log-Rank Mantel–Cox). There was no statistically significant difference in fatigue survival between the Zglz, Zctrl, and Zinf-comp groups. The Zinf-tens group presented a significantly higher failure load when compared to the other groups and exhibited a different failure mode. The experimental glass effectively infiltrated the zirconia, enhancing structural reliability, altering the failure mode, and improving load-bearing capacity over more cycles, particularly in the group where the glass was infiltrated into the tensile surface of the zirconia. Glass infiltration into 5Y-PSZ zirconia significantly enhanced structural reliability and the ability to withstand loads over an increased number of cycles. This approach has the potential to increase the durability of zirconia restorations, reducing the need for replacements and save time and resources, promoting efficiency in clinical practice.
Keywords: 5Y-PSZ Zirconia; Experimental glass; Fatigue survival; Glass infiltration; Kaplan–Meier analysis; Structural reliability